Naturopathic approaches to irritable bowel syndrome: protocol for a prospective observational study in academic teaching clinics - Joshua Z. Goldenberg; Amie Steel; Andrew Day; Christina Yap; Ryan Bradley; Kieran Cooley (Integrative Medicine Research)
Background: Irritable bowel syndrome (IBS) is a common functional bowel disorder with a worldwide prevalence estimated between 10% and 20%. It has a significant impact on quality of life and societal expense. While there are pharmaceutical options available, few can be reliably recommended. Many IBS sufferers turn to complementary and alternative medicine including naturopathy. Naturopathic approaches to IBS are poorly studied to date. Methods: We aim to describe naturopathic approaches to IBS as well as establish pilot data on before and after changes in validated IBS instruments. The study will employ a multi-centered, international, prospective, observational, naturalistic design. The uncontrolled before-and-after study will examine the outcomes associated with individualized, whole system naturopathic care as determined by each provider. We will recruit adult patients diagnosed with IBS and presenting to a participating naturopathic academic teaching clinic. Participants’ IBS symptoms will be measured using validated instruments (IBS-SSS and IBS-AR). Quality of life will be measured by using the PROMIS-29 profile. Adverse events will be tracked, as followed for treatment descriptions. Our primary outcomes will be before-and-after differences using week twelve as the primary endpoint. A p values will be set at 0.05, and descriptive and summary data will be presented. Discussion: This study is designed to plug significant evidence gaps and to gather preliminary evidence to guide the design of a follow-up randomized active controlled trial.Australia and New Zealand Clinical Trial Registration Number: ACTRN12617001413314Version 1.1 Keywords: Irritable bowel syndrome, Naturopathy, Complementary therapies, Observational studies, Protocol